LT Materials and Activities Production Sessions - Castillo, Maria; Piantzi, Leticia (CIEX JOURNAL, 2017)
The area of language teaching materials has been evolving continuously, starting from the design and production of very traditional teaching aids to alternative teaching tools designed with the help of technology. In these sessions, participants will analyze the fundamentals to design alternative language teaching materials. Next, they will produce some alternative didactic materials such as: tan gram, posters, cartoons, books, and technology based materials, among others.